Updates and Debate Concerning Margin Adequacy and Management following Breast-Conserving Surgery - Serena Bertozzi; Ambrogio P Londero; Jose Andres Diaz Nanez; Francesco Leone; Barbara Baita; Lucia La Verghetta; Milena Nobile; Daria Almesberger; Carla Cedolini (IMR Press, 2022)
Objective: Breast-conserving surgery (BCS) experienced a significant surge during the last decades due to the increase of early breast cancer detection. Central to the discussion is margin adequacy which represents one of the most significant predictive factors for local relapse. This paper aims to shed light on the problem of margins in breast surgery. Mechanism: We performed a systematic narrative review of the literature by conducting a search using Medline/PubMed, Scopus, and Embase. The following keywords were considered: "breast-conserving surgery" AND "margins"/"margin". Findings in Brief: In the case of invasive breast cancer, "no ink on tumor" can be considered an adequate margin, while for ductal carcinoma in situ (DCIS), a distance of 2 mm from tumor should be obtained. Many novel tools have been developed based both on the latest radiological imaging techniques and on the tissue expression of certain markers, with the aim of precise navigation of tumor excision and intraoperative evaluation of cavity excision margins. Oncoplastic surgery can be considered oncologically safe while improving the cosmetic outcome and patients' quality of life. The appropriate use of adjuvant treatments in the context of a multidisciplinary and personalized management of breast cancer is the only means to omit a second intervention in some carefully selected cases. Conclusions: Debate still exists concerning the definition of adequate clear margin following BCS for DCIS. Further studies are required to better assess multimodal treatment approaches in this condition.